Implementasi Tanggung Jawab Sosial Perusahaan (Corporate Social Responsibility) pada PT.Kalirejo Lestari - Tami Rusli (Universitas Bandar Lampung (UBL), 2012)
In this time company do not only having legal and economic obligations to stockholder ( shareholders) but also obligations to other partys which is have importance ( stakeholders) pass program of CSR. CSR meant to push behavioral corporate world [of] me more ethical by giving contribution to development of economics in running its effort activity. included of CSR into law and regulation of change over paradigm him of CSR, what initialy initialy have the character of voluntaryly ( voluntary) turn into a[n obligation ( mandatory). As for problem of this research is arrangement concerning social responsibility of company ( CSR) in Indonesia and also social responsibility implementation [of] company ( CSR) at PT. Everlasting Kalirejo. Result of research indicate that Arrangement concerning CSR in Indonesia for example in arranging in Code Number 19 Year 2003 about Body of[is Effort Publik Ownwrship, [Code/Law] Number 25 Year 2007 about Cultivation Of Capital, Code Number 40 Year 2007 about Limited Liability, Code Number 4 Year 2009 about Mineral and Coal, and also Code Number 32 Year 2009 about Protection and Management Of Environment. Implementation of CSR at PT. Kalirejo have walked is good enough, but still there is no Performance Report of CSR done by company. Execution of CSR done by companys in Indonesia still many in the form of development community, charity, or activitys of filantropi. And frequently activity of the CSR not yet been related to three element 3BL becoming key of development of have continuation